PRIVACY-PRESERVING BASED ON CHARACTERISTIC ENCRYPTION USING AUDITABLE ACCESS THROUGH ENCRYPTED DATA IN CLOUD ENVIRONMENT. - J., Raja; S., Mukilan; S., Anbumani; P. S., Ratan Rana (Proteus, 2022)
Cloud Computing is a sort of parallel isolated framework with an arrangement of interconnected and virtualized systems. Commonly, the cloud storage is called storage as a service, implies that an encryption standard gives the critical possibility to the logical with current selection and distribution of the information sharing worldview in conveyed frameworks. Key management is an essential component of cryptographic read access control. Managing a large number of secret keys is a challenge for the organization that outsourced its data. A fundamental objective of key management is to reduce the secret key storage with each authorized user. To this end, this paper discusses an essential key management hierarchy for better data storage with privacy preserving in the cloud environment. We critically evaluate two types of key management hierarchy for data outsourcing in the cloud, there are user based auditable hierarchy and resource-based auditable hierarchy. The support for data dynamics through the broadest types of information act, for example, square adjustment, addition, and cancellation are likewise a considerable advance toward common sense since services in Cloud Computing is not restricted to document. This result challenges a common belief that resource based hierarchies require significantly more storage than the existing one. We also show that user-based hierarchies are more efficient regarding computation and communication cost as compared to all other existing auditability concerning effective result in cloud environment. The prediction of our outcomes measures the encryption models with key replacement make essential security to prevent vulnerabilities. Finally, the result produces the smallest time for data storage with benefit access to give the security system in high requirement.